2002
DOI: 10.1002/bies.10201
|View full text |Cite
|
Sign up to set email alerts
|

Cell signaling through membrane mucins

Abstract: MUC1 and MUC4 are the two membrane mucins that have been best characterized. Although they have superficially similar structures and have both been shown to provide steric protection of epithelial surfaces, recent studies have also implicated them in cellular signaling. They act by substantially different mechanisms, MUC4 as a receptor ligand and MUC1 as a docking protein for signaling molecules. MUC4 is a novel intramembrane ligand for the receptor tyrosine kinase ErbB2/HER2/Neu, triggering a specific phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
214
4
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(221 citation statements)
references
References 45 publications
2
214
4
1
Order By: Relevance
“…In these bacteria, this enzyme is critical for degradation of milk casein to oligopeptides that then serve as source of amino acids (30). Although the role of this protease in NCC 533 is unclear, it may enhance acquisition of amino acids in the competitive GIT environment or participate in host interactions via proteolytic cleavage of glycoproteins in the mucus layer (31).…”
Section: Resultsmentioning
confidence: 99%
“…In these bacteria, this enzyme is critical for degradation of milk casein to oligopeptides that then serve as source of amino acids (30). Although the role of this protease in NCC 533 is unclear, it may enhance acquisition of amino acids in the competitive GIT environment or participate in host interactions via proteolytic cleavage of glycoproteins in the mucus layer (31).…”
Section: Resultsmentioning
confidence: 99%
“…25,26 In addition to their role in providing barriers that can limit direct access of other cells 26 or large molecules 27,28 to the associated cell surface, recent studies have also implicated them in cellular signaling. By activating growth factor receptors, such as ErbB2, 29 or serving as docking sites for intracellular proteins, 30 they have been shown to alter cellular behavior, repress apoptosis, enhance proliferative signaling or lead to diminished cell-cell adhesion. 26,29,[31][32][33] Given the significant correlation of low D2-40 immunoreactivity with lymphatic invasion, it is intriguing to hypothesize that the M2A antigen may also have functions affecting cellular behavior, such as cellcell adhesion or invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The transmembrane subunit ASGP-2 is N-glycosylated and has a molecular mass of ϳ120 kDa. Transfection studies have shown that Muc4/SMC is a multifunctional protein with anti-adhesive (4), anti-recognition (5), and signal regulation functions (6,7), all of which are important characteristics of both normal epithelia and tumors. Immunocytochemical analyses show the presence of Muc4/ SMC in a number of different vulnerable epithelia, including those of the female reproductive tract, airway, ocular surface, and mammary gland (8).…”
Section: Muc4/smcmentioning
confidence: 99%